Penerapan Metode Quality Function Deployment dalam Memenuhi Kepuasan Konsumen pada Industri Komponen Otomotif - Ikrimah Nur Azizah; Rissa Nur Lestari; Humiras Hardi Purba (Department Industrial Engineering, University of Muhammadiyah Malang, 2018)
Manufacture industries that produce automotive components are conducting studies about things that can improve customer satisfaction. This is due to customer claims regarding quality and product delivery. Another problem is the not yet optimal Just In Time (JIT) system implemented by the Company. To overcome these problems, then in this study conducted customer satisfaction analysis using the method of Quality Function Deployment (QFD). The results of the study will be used as materials for improvement on Machine Capacity, material specification, store and work instructions process. The results found priority issues based on House of Quality that has been made, should be done on the machine capacity, material specification, and storage system and then proceeded with the work instructions process.